Response of chili (Capsicum annuum L.) to bioslurry fertilization and enrichment of Trichoderma asperellum on planting media. Issue 1 (April 2020) - Kaimuddin,; Dermawan, R; Rahman, A R; Syam'un, E; Dungga, N E; Yanti, C W B; Mulawarman, A
Abstract: This study aimed to determine the response of chili plants ( Capsicum annuum L.) to the treatment of bioslurry fertilizer and enrichment of Trichoderma asperellum on planting media. The study was conducted from October 2017 to January 2018 and set based on randomized block design (RBD). The treatment of Trichoderma asperellum as the first factor consisted of five levels, namely: 0 g plant −1 (control), 5, 10, 15, and 20 g plant −1 . The second factor was bioslurry fertilization treatment consisted of five levels, namely: 0 mL L −1 (control), 100, 200, 200, and 400 mL L −1 per application. The results show that the application of Trichoderma asperellum 10 g plant −1 gave the highest fruit length of 12.03 cm. The interaction between Trichoderma asperellum 10 g plant −1 and 100 mL L −1 bioslurry per application showed the best results on the highest number of productive branches (45.17 stems), the highest number of harvested fruit (12.17 fruits), and the heaviest fruit weight (129.82 g).